A piezoelectric nanogenerator and a preparation method and application in real-time monitoring of fruit and vegetable transportation
By preparing BCZT ceramic nanoparticles combined with cellulose acetate via a solid-state method and then using electrospinning, a piezoelectric nanogenerator was constructed. This solved the problems of poor electrical output performance and environmentally unfriendly materials in existing technologies, enabling real-time monitoring and environmentally friendly electrical signal conversion during fruit and vegetable transportation.
Patent Information
- Application Number
- CN202611306876.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-11-03
AI Technical Summary
Existing piezoelectric nanogenerators have poor electrical output performance during fruit and vegetable transportation, making it difficult to achieve real-time monitoring of mechanical conditions such as vibration and impact. Furthermore, the materials are not environmentally friendly and lack flexibility and adaptability.
BCZT ceramic nanoparticles were prepared by solid-state method and combined with cellulose acetate. Piezoelectric nanogenerators were constructed by electrospinning process. The flexibility of cellulose acetate and the high voltage electroactivity of BCZT ceramics were used to form a composite film, which was then assembled with copper electrodes and conductive copper wires.
It achieves efficient conversion of weak mechanical energy into electrical signals, provides stable electrical output performance, is suitable for real-time monitoring during fruit and vegetable transportation, and is environmentally friendly and flexible, overcoming the shortcomings of existing technologies.
Smart Images

Figure CN123034745A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nanogenerator technology, specifically relating to a piezoelectric nanogenerator, its preparation method, and its application in real-time monitoring of fruit and vegetable transportation. Background Technology
[0002] With the continuous development of smart logistics and intelligent sensing technologies, the quality and safety of fruits and vegetables during post-harvest logistics and transportation are becoming increasingly prominent. Fruits and vegetables inevitably experience dynamic mechanical forces such as vibration, impact, and compression during transportation. These external stimuli are characterized by their suddenness and continuity; if they cannot be sensed and fed back in real time and online, they are highly susceptible to tissue damage and quality deterioration. Therefore, real-time, continuous, and dynamic monitoring of the mechanical state during fruit and vegetable logistics and transportation has become a key technological requirement for ensuring transportation safety and reducing losses. However, existing fruit and vegetable transportation status monitoring devices mostly rely on battery-powered sensing systems, which not only suffer from limited power supply lifespan and high maintenance costs, but also struggle to achieve real-time response and continuous monitoring of instantaneous vibration and impact events during transportation, failing to meet the real-time requirements of practical logistics applications. Meanwhile, with the rapid development of flexible electronics, self-powered sensors, and real-time sensing systems, how to fully utilize the weak mechanical energy widely present during fruit and vegetable transportation to achieve real-time sensor operation and continuous monitoring has attracted widespread attention from researchers. Traditional energy harvesting methods such as wind, hydro, and solar power are typically suitable for large-scale, stable environments, but they are still difficult to effectively utilize the randomly distributed and transiently changing minute mechanical energy generated during logistics and transportation. Against this backdrop, nanogenerator technology, capable of generating instantaneous electrical responses to mechanical stimuli, is gradually becoming an important technological approach for constructing real-time monitoring systems.
[0003] Among the many types of nanogenerators, piezoelectric nanogenerators (PENGs) and triboelectric nanogenerators (TENGs) are considered the two most promising for application. PENGs can immediately generate electrical signals in response to external mechanical stimuli, exhibiting characteristics such as fast response speed and high synchronization between signal and mechanical stimulation. They are particularly suitable for real-time, continuous monitoring of logistics transportation conditions such as vibration and shock. Existing piezoelectric nanogenerators are typically composed of piezoelectric ceramics and flexible polymer materials, such as lead zirconate titanate, potassium sodium niobate, and polyvinylidene fluoride (PVDF). While possessing high electrical output performance, they generally suffer from environmental unfriendliness, insufficient flexibility, and poor safety, limiting their application in scenarios such as fruit and vegetable logistics where material safety and real-time monitoring reliability are paramount. Chinese patent application CN119287558B discloses a branched heterostructure piezoelectric fiber, a piezoelectric nanogenerator, its preparation method, and its applications, using PVDF as the flexible matrix material. Polyvinylidene fluoride (PVDF) is a fluorine-containing polymer material. Although it possesses good piezoelectric properties and flexibility, it is non-biodegradable and has poor environmental friendliness, limiting its application in scenarios such as fruit and vegetable logistics where material safety requirements are high. Chinese patent application CN119401850B discloses a coupled biomass-based nanogenerator combining PENG and TENG and its preparation method. While the short-circuit current and open-circuit voltage of the prepared nanogenerator are improved compared to pure cellulose films, its electrical signal output strength is still limited for real-time sensing of weak vibrations, impacts, and other mechanical stimuli during fruit and vegetable transportation, making it difficult to meet the needs of high-sensitivity real-time monitoring.
[0004] Therefore, developing a piezoelectric self-powered sensor based on environmentally friendly materials, possessing flexibility, and capable of generating rapid and stable electrical signals in response to mechanical stimuli during transportation is of great significance for achieving real-time, online, and continuous monitoring of the status of fruit and vegetable logistics transportation. However, the existing biomass-based piezoelectric materials have limited electrical output capabilities, making it difficult to achieve highly sensitive, real-time status sensing while maintaining flexibility, and further optimization and design are still needed. Summary of the Invention
[0005] In order to overcome the shortcomings of the prior art, the present invention aims to provide a piezoelectric nanogenerator and its preparation method, as well as its application in real-time monitoring of fruit and vegetable transportation, so as to solve the technical problem that the existing pure cellulose film can only provide a single form of electrical output and has poor electrical output performance, making it difficult to meet the technical requirements for real-time monitoring of mechanical conditions such as vibration and impact during fruit and vegetable transportation.
[0006] To achieve the above objectives, the present invention employs the following technical solution: This invention discloses a method for preparing a piezoelectric nanogenerator, comprising: BCZT ceramic T-phase nanoparticle filler and BCZT ceramic R-phase nanoparticle filler were respectively added to cellulose acetate solution and dispersed by ultrasonication to obtain cellulose acetate / BCZT electrospinning precursor solution. Electrospinning was performed on the cellulose acetate / BCZT electrospinning precursor solution, and after drying, cellulose acetate / BCZT ceramic composite film was obtained. After cutting the cellulose acetate / BCZT ceramic composite film, it is attached between two copper electrodes, and a conductive copper wire is spirally coiled and attached to the two copper electrodes to obtain a piezoelectric nanogenerator.
[0007] Preferably, the BCZT ceramic T-phase nanoparticle filler is prepared by a solid-state method. The preparation method includes: mixing BaCO3, CaCO3, ZrO2 and TiO2, and then sequentially subjecting the mixture to ball milling, drying, grinding, sieving, pre-calcination, secondary ball milling, granulation, filtration, pressing, debinding, sintering, secondary grinding, tertiary ball milling and drying to obtain the BCZT ceramic T-phase nanoparticle filler; the molar ratio of BaCO3, CaCO3, TiO2 and ZrO2 is (16~17):(2~3):(17~18):(1~2); BCZT ceramic R-phase nanoparticle filler was prepared by a solid-state method. The preparation method included: mixing BaCO3, CaCO3, ZrO2 and TiO2, and then sequentially subjecting the mixture to ball milling, drying, grinding, sieving, pre-calcination, secondary ball milling, granulation, filtration, pressing, debinding, sintering, secondary grinding, tertiary ball milling and drying to obtain BCZT ceramic R-phase nanoparticle filler; the molar ratio of BaCO3, CaCO3, TiO2 and ZrO2 was (19~20):(1~1.5):(18~19):(2~3); The ball milling time was 8-16 hours; the secondary ball milling time was 6-10 hours; granulation was carried out by adding polyvinyl alcohol; the granulated ceramics were filtered through a 120-mesh sieve to obtain ceramic particles with a diameter of 0.125-0.28 mm; the discharge temperature was 790-810℃, the heating rate was 4-5℃ / min, and the holding time was 2 hours; the secondary grinding time was 30-60 minutes, and the tertiary ball milling time was 1-2 hours.
[0008] More preferably, in the preparation of BCZT ceramic T-phase nanoparticle filler, the pre-firing temperature is 1445~1455℃; the sintering temperature is 1470~1530℃, the heating rate is 4~5℃ / min, and the holding time is 2h.
[0009] More preferably, in the preparation of BCZT ceramic R-phase nanoparticle filler, the pre-firing temperature is 1450~1520℃; the sintering temperature is 1450~1510℃, the heating rate is 4~5℃ / min, and the holding time is 2h.
[0010] Preferably, the method for preparing cellulose acetate solution includes: mixing N,N-dimethylacetamide solution and acetone solution to prepare a mixed solvent, adding polyvinylpyrrolidone and stirring, then adding cellulose acetate and continuing to stir to obtain cellulose acetate solution.
[0011] More preferably, the mass ratio of N,N-dimethylacetamide solution to acetone solution is (3~4):(1~2); the mass ratio of polyvinylpyrrolidone to cellulose acetate is 0.24:0.96; the stirring speed before adding cellulose acetate is 500~600 r / min for 30~40 min; and the stirring speed after adding cellulose acetate is 500~600 r / min for 4~4.5 h.
[0012] Preferably, in the cellulose acetate solution, the mass ratio of BCZT ceramic T-phase nanoparticle filler to BCZT ceramic R-phase nanoparticle filler is (0.003~0.01):(0.003~0.01); the ultrasonic dispersion time is 4~5h.
[0013] Preferably, the conditions for electrospinning include: syringe inner diameter of 0.41 mm, injection speed of 0.01 mm / s, voltage of 14~18 kV, roller speed of 500~700 rpm, and receiving distance of 20~23 cm; the drying conditions are to place at room temperature for 12 hours or more.
[0014] The present invention also discloses a piezoelectric nanogenerator, which is prepared by the above-described method for preparing a piezoelectric nanogenerator.
[0015] The present invention also discloses the application of the above-mentioned piezoelectric nanogenerator in real-time monitoring of fruit and vegetable transportation.
[0016] Compared with the prior art, the present invention has the following beneficial effects: This invention discloses a method for preparing a piezoelectric nanogenerator. The method involves preparing BCZT ceramic T-phase nanoparticle fillers and BCZT ceramic R-phase nanoparticle fillers by solid-state method, introducing them into cellulose acetate electrospinning solution, constructing a nanofiber composite film by electrospinning process, and then assembling the piezoelectric nanogenerator by bonding copper electrodes and winding conductive copper wires. Cellulose acetate, as a flexible biomass matrix material, possesses excellent film-forming properties and mechanical flexibility, and is environmentally friendly and biodegradable, overcoming the non-renewable drawbacks of traditional piezoelectric polymer materials. The introduction of BCZT piezoelectric ceramics significantly enhances the device's piezoelectric response to external mechanical stimuli, and the dual-phase composite design of T and R phases synergistically improves piezoelectric output performance. The high-voltage electric field induced by electrospinning during the process, along with the orientation of BCZT piezoelectric dipoles, improves the consistency and stability of the piezoelectric response, ensuring good time synchronization between the output signal and changes in external mechanical stimuli. The nanofiber network structure formed by electrospinning endows the composite film with high flexibility and stress sensitivity, allowing for significant deformation even under minor mechanical stimuli, thus enabling rapid and synchronous electrical signal responses to dynamic external forces such as vibration and impact. The piezoelectric nanogenerator prepared in this invention has an open-circuit voltage of approximately 46V and a short-circuit current of approximately 3.4μA, and exhibits stable output characteristics under different frequency loading conditions, effectively solving the technical problems of limited electrical output capability and difficulty in achieving highly sensitive real-time state sensing while maintaining flexibility in existing biomass-based piezoelectric materials.
[0017] This invention discloses a piezoelectric nanogenerator that is small in size, low in cost, flexible, biomass-friendly, and has stable electrical output performance. The nanogenerator uses a cellulose acetate / BCZT ceramic composite film as its core functional layer, with copper electrodes attached to both sides and conductive copper wire spirally wound to extract electrical signals. The structure is simple and reliable. Due to the synergistic effect of the flexible nature of the cellulose acetate matrix and the high-voltage electroactivity of the BCZT piezoelectric ceramic, this device can effectively convert the weak mechanical energy widely present during fruit and vegetable transportation, such as vibration, impact, and compression, into electrical signals, achieving self-powered sensing without external power supply. Its electrical output performance, with an open-circuit voltage of approximately 46V and a short-circuit current of approximately 3.4μA, is significantly superior to existing biomass-based piezoelectric materials, providing sufficient electrical energy for subsequent signal processing and wireless transmission. This provides a reliable device foundation for real-time, online, and continuous monitoring of the status of fruit and vegetable logistics transportation, and has promising application prospects.
[0018] This invention discloses the application of a piezoelectric nanogenerator in real-time monitoring of fruit and vegetable transportation. When used for real-time monitoring of vibration and / or impact mechanical conditions during fruit and vegetable transportation, the piezoelectric nanogenerator can rapidly respond to randomly distributed and instantaneously changing weak mechanical stimuli during transportation. Its short response time enables real-time capture of sudden vibration and impact events, overcoming the shortcomings of traditional battery-powered sensing systems that struggle to respond to instantaneous events in real time. This piezoelectric nanogenerator is a self-powered sensing device, requiring no external power source or battery power, fundamentally solving the practical engineering problems of limited power supply lifespan and high maintenance costs. The main materials of the piezoelectric nanogenerator are cellulose acetate biomass matrix and lead-free BCZT piezoelectric ceramics, exhibiting excellent environmental friendliness and biosafety, making it suitable for fruit and vegetable logistics scenarios with high material safety requirements. It maintains stable electrical output under different frequency loading conditions, and its electrical output performance shows no significant attenuation under long-term application, ensuring the continuity and reliability of real-time monitoring data. This effectively reduces losses during fruit and vegetable transportation and improves the quality and safety level of logistics. Attached Figure Description
[0019] Figure 1 The images show the composition and morphology of the various materials prepared in Example 1 of this invention; (a) is the XRD pattern of BCZT ceramic T-phase nanoparticle filler and BCZT ceramic R-phase nanoparticle filler; (b) is the Rietveld refined image of the XRD data of BCZT ceramic T-phase nanoparticle filler and BCZT ceramic R-phase nanoparticle filler; (c) is the SEM image of BCZT ceramic R-phase nanoparticle filler; and (d) is the SEM image of cellulose acetate / BCZT ceramic composite film. Figure 2 The following are performance graphs of the piezoelectric nanogenerator prepared in Example 1 of the present invention, measured at different frequencies and under different forces; wherein, (a) is the short-circuit current; (b) is the open-circuit voltage; (c) is the long-term current output graph; and (d) is the response time. Figure 3 The figures below show specific applications of the piezoelectric nanogenerators prepared in Comparative Examples 2 and 3 of this invention; (a) is a schematic diagram of transportation vibration simulation; (b) is a schematic diagram of the arrangement of the six-sided sensors; (c) is a physical image of the completed intelligent packaging monitoring system; (d1) is the short-circuit current output result of the packaging box under slight shaking conditions; (d2) is the open-circuit voltage output result of the packaging box under slight shaking conditions; (e1) is the short-circuit current output result of the packaging box under severe shaking conditions; and (e2) is the open-circuit voltage output result of the packaging box under severe shaking conditions. Detailed Implementation
[0020] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] Unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined to form new technical solutions.
[0022] Unless otherwise specified, all the technical features and preferred features mentioned herein can be combined to form new technical solutions.
[0023] In this invention, unless otherwise specified, percentage (%) or parts refer to weight percentage or parts relative to the composition.
[0024] Unless otherwise specified, the components or preferred components involved in this invention can be combined with each other to form new technical solutions.
[0025] In this invention, unless otherwise specified, the numerical range "a~b" is an abbreviation for any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "6~22" indicates that all real numbers between "6~22" have been listed in this document, and "6~22" is simply an abbreviation for these numerical combinations.
[0026] The "scope" disclosed in this invention can be in the form of a lower limit and an upper limit, and can be one or more lower limits and one or more upper limits, respectively.
[0027] The term “and / or” as used in this invention refers to any combination of one or more of the associated listed items, as well as all possible combinations, and includes such combinations.
[0028] Unless otherwise stated, the technical and scientific terms used herein have the same meanings as those familiar to those skilled in the art. Furthermore, any methods or materials similar to or equivalent to those described herein may also be used in this invention.
[0029] The abbreviations used in this invention include: barium calcium titanate (Ba(Ca)(Zr,Ti)O3, BCZT); polydimethylsiloxane (PDMS); polyvinyl alcohol (PVA); polyvinyl pyrrolidone (PVP); N,N-dimethylacetamide (DMAc); and cellulose acetate (CA).
[0030] This invention discloses a method for preparing a piezoelectric nanogenerator. The method involves preparing BCZT ceramic R-phase nanoparticles and BCZT ceramic T-phase nanoparticles using a solid-state method. These nanoparticles are then uniformly dispersed in a cellulose acetate solution to prepare an electrospinning precursor solution. A flexible piezoelectric composite nanofiber film is then fabricated via electrospinning, followed by encapsulation to obtain the piezoelectric nanogenerator. Cellulose acetate, as a flexible biomass matrix material, exhibits excellent film-forming properties and mechanical flexibility. The introduced BCZT ceramic R-phase and T-phase nanoparticles are uniformly distributed within the nanofiber structure under an electric field, significantly enhancing the device's piezoelectric response to external mechanical stimuli. By compounding the prepared BCZT ceramic R-phase and T-phase nanoparticles in a predetermined ratio and introducing them into the cellulose acetate system, the designable and controllable crystal phase composition of the piezoelectric filler is achieved. This step breaks through the existing technical route of directly using a single barium calcium titanate zirconate (Ba(Ca)(Zr,Ti)O3, BCZT) or a naturally formed morphotropic phase boundary (MPB) mixed phase as filler, allowing the synergistic polarization effect between different crystal phases to be fully utilized. Through a combination of independent preparation, proportional compounding, and electrospinning composite construction, the precise control of the crystal phase structure of the flexible piezoelectric composite material and the synergistic enhancement of its piezoelectric properties are achieved. Compared with the prior art, the preparation method of this invention is simple and controllable, and the resulting piezoelectric nanogenerator has the advantages of flexibility, biomass environmental friendliness, and stable electrical output performance. It can effectively convert weak mechanical energy into electrical signals and is suitable for real-time monitoring of mechanical states such as vibration and impact, showing good application prospects.
[0031] BCZT ceramics with the T phase refer to Ba(Ca)(Zr,Ti)O3 piezoelectric ceramics with a tetragonal crystal system (space group P4mm). Their unit cells undergo tetragonal distortion along the c-axis, and spontaneous polarization mainly occurs along... <001> Crystal orientation; BCZT ceramic R phase refers to Ba(Ca)(Zr,Ti)O3 piezoelectric ceramics with a rhombohedral crystal system (space group R3m), whose unit cells undergo rhombohedral distortion along the bulk diagonal, and spontaneous polarization mainly along... <111> Crystal Orientation. The R phase and T phase have different crystal structures and polarization characteristics. This invention uses them as two functional fillers with different piezoelectric response characteristics, and they are compounded according to a preset ratio to achieve synergistic effect of crystal phases and improve the output performance of flexible piezoelectric nanogenerators. The R phase (rhombohedral phase) and T phase (tetragonal phase) in BCZT ceramics are both in the same perovskite structure system. They are different ferroelectric phases formed by different lattice distortion modes and spontaneous polarization directions. The polarization direction of the R phase is along the (111) direction, and the polarization direction of the T phase is along the (001) direction. Both have different piezoelectric response characteristics. The formation of the R phase and T phase is mainly determined by the BCZT raw material ratio and sintering process. The Ba / Ca / Ti / Zr stoichiometric ratio determines the crystal phase type, while the pre-sintering and final sintering temperatures further affect element diffusion, grain growth and lattice stability, thereby stabilizing different crystal phases. Qualitative and quantitative analysis of the crystal phases was performed using XRD testing combined with Rietveld refinement. The crystal structure and phase composition of the R and T phases were confirmed by the splitting of characteristic diffraction peaks and the refinement results.
[0032] The encapsulation process includes: cutting a circular film with a radius of 1.6 cm from a flexible piezoelectric composite nanofiber film; then cutting two copper electrodes with a radius of 1.2 cm; and finally cutting two 20 cm long wires. After removing 5 cm of the insulating adhesive from the two wires to expose the conductive copper wires, the wires are spirally coiled and attached to the two copper electrodes. Finally, they are perfectly aligned and attached to both sides of the circular composite film to obtain the piezoelectric nanogenerator.
[0033] The present invention discloses a method for preparing a piezoelectric nanogenerator, comprising the following steps: Step 1: Preparation of BCZT ceramic T-phase nanoparticle fillers by solid-state method 11) First, add solid BaCO3, CaCO3, ZrO2 and TiO2 into a ball mill jar, and add 30.0g of ball stones and 40.0ml of alcohol to the ball mill jar. Mix them thoroughly, and then place the ball mill jar on a ball mill and mill for 8~16h. After that, put the mixture obtained after milling into an oven to dry it so that the alcohol can be fully evaporated. The molar ratio of BaCO3, CaCO3, TiO2 and ZrO2 is (16~17):(2~3):(17~18):(1~2). 12) First, put the mixture obtained in step 11) into a grinding bowl and grind it to crush the mixed powder. Then, use a sieve to separate the mixed powder from the grinding stone. Pour the separated mixed powder into a crucible, cover the crucible, and put it into a muffle furnace for sintering. Set the temperature of the muffle furnace to 1445~1455℃, the heating rate to 4~5℃ / min, and the holding time to 2h. Then, take out the sintered powder and pour it into a grinding body for grinding so that the powder can be fully dispersed to obtain pre-fired BCZT ceramic T-phase nanoparticles. 13) Add the pre-fired BCZT ceramic particles from step 12) into a ball mill jar, add 30.0g of ball stones and 40.0ml of alcohol, mix them thoroughly, then place the ball mill jar on a ball mill for a second ball milling for 6~10h. After that, put the mixture obtained after ball milling into an oven to dry, so that the alcohol can be fully evaporated, and then add 7~9g of PVA for granulation. 14) Filter the granulated ceramic from step 13) using a 120-mesh sieve. The filtered ceramic particles have a diameter of approximately 0.125-0.28 mm. Weigh 0.45 g of the sample each time using an electronic balance and press it into round green discs using a powder press with a pressure of 20 N. Place the round green discs into a muffle furnace for debinding. Set the temperature to 790-810℃, the heating rate to 4-5℃ / min, and the holding time to 2 h. 15) The ceramic sheets after debinding in 14) are formally sintered. They are placed in a muffle furnace for sintering. The temperature of the muffle furnace is set to 1470~1530℃, the heating rate is 4~5℃ / min, and the holding time is 2h. After that, the sintered ceramic sheets are taken out and poured into a grinding body for grinding. After grinding for 30~60min, they are added to a ball mill jar with a mass ratio of ceramic:ball = 1:1.5. Then, alcohol with a volume ratio of 2 is added. After ball milling for 1~2h, they are placed in an oven to dry, and BCZT ceramic T-phase nanoparticle filler is obtained.
[0034] Step 2: Solid-state preparation of BCZT ceramic R-phase nanoparticle fillers 21) First, add solid BaCO3, CaCO3, ZrO2 and TiO2 into a ball mill jar, and add 30.0g of ball stones and 40.0ml of alcohol to the ball mill jar. Mix them thoroughly, and then place the ball mill jar on a ball mill and mill for 8~16h. After that, put the mixture obtained after milling into an oven to dry it so that the alcohol can be fully evaporated. The molar ratio of BaCO3, CaCO3, TiO2 and ZrO2 is (19~20):(1~1.5):(18~19):(2~3). 22) First, grind the mixture obtained in step 21) in a grinding mortar to crush the powder. Separate the powder from the grinding stones using a sieve. Pour the separated powder into a crucible, cover it, and place it in a muffle furnace for sintering. Set the muffle furnace temperature to 1450~1520℃, the heating rate to 4~5℃ / min, and the holding time to 2h. After sintering, remove the powder and grind it in a grinding mortar to ensure thorough dispersion, thus obtaining pre-sintered BCZT ceramic R-phase nanoparticles. 23) Add the pre-fired BCZT ceramic particles from step 22) into a ball mill jar, add 30.0g of ball stones and 40.0ml of alcohol, mix them thoroughly, then place the ball mill jar on a ball mill for a second ball milling for 6~10h. After that, put the mixture obtained after ball milling into an oven to dry, so that the alcohol can be fully evaporated, and then add 7~9g of PVA for granulation. 24) Select the granulated ceramic from 23) and filter it through a 120-mesh sieve. The filtered ceramic particles have a diameter of about 0.125-0.28 mm. Weigh 0.45 g of the sample each time using an electronic balance and press it into round green discs by a powder press with a pressure of 20 N. Place the round green discs into a muffle furnace for debinding. Set the temperature to 790~810℃, the heating rate to 4~5℃ / min, and the holding time to 2h. 25) The ceramic sheets after debinding in 24) are formally sintered by placing them in a muffle furnace. The temperature of the muffle furnace is set to 1450~1510℃, the heating rate is 4~5℃ / min, and the holding time is 2h. After that, the sintered ceramic sheets are taken out and poured into a grinding body for grinding. After grinding for 30~60min, they are added to a ball mill jar with a mass ratio of ceramic:ball = 1:1.5. Then, alcohol with a volume ratio of 2 is added. After ball milling for 1~2h, they are placed in an oven to dry, and BCZT ceramic R phase nanoparticle filler is obtained.
[0035] Step 3: Preparation of cellulose acetate solution 31) Prepare a solution by mixing N,N-dimethylacetamide (DMAc) solution and acetone solution at a mass ratio of (3~4):(1~2), and then place the mixed solution on a magnetic stirrer and stir at 500~600r / min for 30~40min to obtain a clear, transparent solution without particles; 32) Add polyvinylpyrrolidone (PVP) and cellulose acetate (CA) to the mixed solution obtained in step 31) in a mass ratio of 0.24:0.96, and stir at 500~600 r / min for 4~4.5 h to obtain a viscous cellulose acetate solution.
[0036] Step 4: Preparation of cellulose acetate / BCZT electrospinning precursor solution 41) Add 0.003~0.01g of the BCZT ceramic T phase obtained in step 15) and 0.003~0.01g of the BCZT ceramic R phase obtained in step 24) to a cellulose acetate solution and sonicate for 4~5h to uniformly disperse the ceramic in the cellulose acetate solution to obtain a cellulose acetate / BCZT electrospinning precursor solution.
[0037] Step 5: Preparation of cellulose acetate / BCZT ceramic composite film 51) Inject the precursor solution obtained in step 41) into the needle of a syringe with an inner diameter of 0.41 mm (22G), with an injection speed of 0.01 mm / s, a voltage of 14~18 kV, a roller speed of 500~700 rpm, and a receiving distance of 20~23 cm.
[0038] 52) The composite film obtained in step 51) is dried at room temperature for 12 hours or more to obtain a dried cellulose acetate / BCZT ceramic composite film.
[0039] Step 6: A piezoelectric nanogenerator 61) Cut a circular film with a radius of 1.5 cm from the composite film in step 52). Then cut two copper electrodes with a radius of 1.2 cm. Next, cut two wires with a length of 20 cm. Remove 5 cm of the insulating adhesive from the two wires to expose the conductive copper wires inside. Then, spirally coil and attach them to the two copper electrodes. Finally, attach them to both sides of the circular film in a completely aligned manner. After attachment, a piezoelectric nanogenerator is obtained.
[0040] When BCZT ceramic R-phase nanoparticle fillers and BCZT ceramic T-phase nanoparticle fillers are introduced into the composite system in a certain proportion, a significant synergistic enhancement effect can be generated between the two crystalline phases. The R phase has a strong polarization rotation capability, which can effectively respond to mechanical stress in complex directions, while the T phase has a high longitudinal polarization capability, which can generate a large piezoelectric response under compressive load. After the two crystalline phases are combined, on the one hand, the different polarization directions complement each other, improving the polarization switchable path and the conversion efficiency of mechanical energy to electrical energy; on the other hand, the R / T heterogeneous interface increases, which easily forms interface polarization and charge accumulation under external force, improving the output voltage and current. At the same time, the different crystalline phases respond differently to mechanical stress, which is conducive to the uniform transmission and distribution of stress in the composite system, further enhancing the overall piezoelectric response. Therefore, by reasonably controlling the ratio of R phase to T phase, the synergistic effect of the crystalline phases can be fully utilized, so that the composite material can obtain comprehensive performance superior to that of a single R phase or a single T phase. Tests show that the output performance is optimal when the R / T ratio is 1:1, indicating that the two crystalline phases can achieve the best synergistic effect at this ratio.
[0041] This invention prepares BCZT ceramic R-phase nanoparticles and BCZT ceramic T-phase nanoparticles via a solid-state method, introduces them into a cellulose acetate solution to form an electrospinning precursor, and constructs a nanofiber composite film using electrospinning. The film is then encapsulated in PDMS to fabricate a flexible piezoelectric nanogenerator. This preparation method not only achieves uniform dispersion of piezoelectric functional materials in a biomass matrix but also simultaneously controls the microstructure and polarization orientation during film formation, providing excellent piezoelectric response performance for the device. The nanofiber network structure formed during electrospinning gives the composite film high flexibility and stress sensitivity, allowing it to undergo significant deformation under minor mechanical stimuli. This enables a rapid and synchronous electrical signal response to dynamic external forces such as vibration and impact, significantly improving the device's real-time sensing capability against external mechanical stimuli. Simultaneously, the high-voltage electric field applied during electrospinning induces the orientation of the fibers and BCZT piezoelectric dipoles, improving the consistency and stability of the piezoelectric response and ensuring good time synchronization between the output signal and changes in external mechanical stimuli, making it suitable for continuous, online, real-time monitoring scenarios. Furthermore, the PDMS encapsulation layer protects and buffers the device, effectively improving its durability and environmental stability under complex transportation conditions. This ensures the device maintains stable electrical output even under long-term operating conditions, thereby guaranteeing the reliability of real-time monitoring data. The piezoelectric nanogenerators obtained using the above preparation method exhibit stable output characteristics under different frequency loading conditions, demonstrating their good operational stability and broad application prospects.
[0042] The present invention discloses a piezoelectric nanogenerator prepared by the above-mentioned method. This nanogenerator is small in size, low in cost, and has high electrical output performance. Under a fixed force of 2N and an excitation frequency of 5Hz, the open circuit voltage of the piezoelectric nanogenerator prepared in Example 1 is about 46V and the short circuit current is about 3.4μA.
[0043] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0044] Example 1 A method for fabricating a piezoelectric nanogenerator includes the following steps: 1) Solid-state method for preparing BCZT ceramic T-phase nanoparticle fillers First, 12.560g of solid BaCO3, 1.124g of CaCO3, 0.923g of ZrO2, and 5.393g of TiO2 were added to a ball mill jar, along with 30.0g of grinding stones and 40.0ml of alcohol. The mixture was thoroughly combined, and then the jar was placed in a ball mill and milled for 12 hours. After milling, the resulting mixture was dried in an oven to allow the alcohol to evaporate completely. The mixture was then ground in a grinding bowl to pulverize the powder. The powder was then separated from the grinding stones using a sieve. The separated powder was poured into a crucible, covered, and sintered in a muffle furnace at 1450℃ with a heating rate of 5℃ / min and a holding time of 2 hours. The sintered powder was then removed and ground in a grinding bowl to ensure thorough dispersion, yielding pre-sintered BCZT ceramic T-phase nanoparticles. The pre-fired BCZT ceramic particles were added to a ball mill jar with 30.0g of ball stones and 40.0ml of alcohol. The mixture was thoroughly mixed, and then the ball mill jar was placed on a ball mill for a second ball milling for 8 hours. After that, the mixture obtained after ball milling was placed in an oven to dry, allowing the alcohol to evaporate completely. Then, 7.8g of PVA was added for granulation.
[0045] The granulated ceramics were filtered through a 120-mesh sieve, and the filtered ceramic particles had a diameter of approximately 0.125-0.28 mm. Each time, 0.45 g of sample was weighed using an electronic balance and pressed into round green discs by a powder press with a pressure of 20 N. The round green discs were then placed in a muffle furnace for debinding, with the temperature set at 800℃, a heating rate of 5℃ / min, and a holding time of 2 h.
[0046] After debinding, the ceramic sheets were formally sintered in a muffle furnace at a temperature of 1500℃, a heating rate of 5℃ / min, and a holding time of 2h. The sintered ceramic sheets were then removed and ground in a grinding chamber for 40min. After grinding, they were added to a ball mill jar at a mass ratio of ceramic to ball milling stone of 1:1.5, and then alcohol at a volume ratio of 2 was added. After ball milling for 1h, the jar was dried in an oven to obtain BCZT ceramic T-phase nanoparticle filler.
[0047] 2) Solid-state method for preparing BCZT ceramic R-phase nanoparticle fillers First, 13.545g BaCO3, 0.362g CaCO3, 0.89g ZrO2, and 5.204g TiO2 in solid form were added to a ball mill jar, along with 30.0g of grinding stones and 40.0ml of alcohol. The mixture was thoroughly combined, and then the jar was placed in a ball mill and milled for 12 hours. After milling, the resulting mixture was dried in an oven to allow the alcohol to evaporate completely. The mixture was then ground in a grinding bowl to pulverize the powder. The powder was then separated from the grinding stones using a sieve. The separated powder was poured into a crucible, covered, and sintered in a muffle furnace at 1500℃ with a heating rate of 5℃ / min and a holding time of 2 hours. The sintered powder was then removed and ground in a grinding bowl to ensure thorough dispersion, yielding pre-sintered BCZT ceramic R-phase nanoparticles. The pre-fired BCZT ceramic particles were added to a ball mill jar with 30.0g of ball stones and 40.0ml of alcohol. The mixture was thoroughly mixed, and then the ball mill jar was placed on a ball mill for a second ball milling for 8 hours. After that, the mixture obtained after ball milling was placed in an oven to dry, allowing the alcohol to evaporate completely. Then, 7~9g of PVA was added for granulation.
[0048] The granulated ceramics were filtered through a 120-mesh sieve, and the filtered ceramic particles had a diameter of approximately 0.125-0.28 mm. Each time, 0.45 g of sample was weighed using an electronic balance and pressed into round green discs by a powder press with a pressure of 20 N. The round green discs were then placed in a muffle furnace for debinding, with the temperature set at 800℃, a heating rate of 5℃ / min, and a holding time of 2 h.
[0049] After debinding, the ceramic sheets were formally sintered in a muffle furnace at a temperature of 1480℃, a heating rate of 5℃ / min, and a holding time of 2h. The sintered ceramic sheets were then removed and ground in a grinding chamber for 40min. After grinding, the sheets were added to a ball mill jar at a mass ratio of ceramic to ball milling stone of 1:1.5, and then alcohol at a volume ratio of 2 was added. After ball milling for 1h, the sheets were dried in an oven to obtain BCZT ceramic R-phase nanoparticle filler.
[0050] 3) Preparation of cellulose acetate solution Prepare a solution by mixing 6.66g of DMAc solution with 3.33g of acetone solution at a mass ratio of 3:2, then add 0.24g of PVP, and then place the mixture on a magnetic stirrer and stir at 500r / min for 40min to obtain a clear, transparent, particle-free solution. Add 0.96 g CA to the obtained mixed solution and stir at 500 r / min for 4.5 h to obtain a viscous cellulose acetate solution.
[0051] 4) Preparation of cellulose acetate / BCZT electrospinning precursor solution 0.005g of BCZT ceramic T phase and 0.005g of BCZT ceramic R phase were added to a cellulose acetate solution and sonicated for 5 hours to uniformly disperse the ceramics in the cellulose acetate solution, thus obtaining a cellulose acetate / BCZT electrospinning precursor solution.
[0052] 5) Preparation of cellulose acetate / BCZT ceramic composite films The obtained precursor solution was injected into the needle of a syringe with an inner diameter of 0.41 mm (22G), the injection speed was 0.01 mm / s, the voltage was 18 kV, the roller speed was 700 rpm, and the receiving distance was 23 cm.
[0053] The obtained composite film was dried at room temperature for 12 hours or more to obtain a dried cellulose composite film.
[0054] 6) Fabrication of a piezoelectric nanogenerator A circular film with a radius of 1.5 cm was cut from the dried cellulose acetate / BCZT ceramic composite film. Two copper electrodes with a radius of 1.2 cm were then cut, followed by two 20 cm long wires. The insulating adhesive on the two wires was removed by 5 cm to expose the conductive copper wires inside. These wires were then spirally coiled and attached to the two copper electrodes, and finally, perfectly aligned, attached to both sides of the circular composite film. After attachment, a piezoelectric nanogenerator was obtained.
[0055] Comparative Example 1 A method for fabricating a piezoelectric nanogenerator includes the following steps: 1) Preparation of cellulose acetate precursor solution Prepare a solution by mixing 6.66g of DMAc solution with 3.33g of acetone solution at a mass ratio of 3:2, then add 0.24g of PVP, and then place the mixture on a magnetic stirrer and stir at 500r / min for 30min to obtain a clear, transparent, particle-free solution. Add 0.96 g CA to the obtained mixed solution and stir at 500 r / min for 4 h to obtain a viscous cellulose acetate solution.
[0056] 2) Preparation of cellulose acetate film The obtained precursor solution was injected into the needle of a syringe with an inner diameter of 0.41 mm (22G), the injection speed was 0.01 mm / s, the voltage was 18 kV, the roller speed was 700 rpm, and the receiving distance was 20 cm.
[0057] The obtained composite film was dried at room temperature for 12 hours or more to obtain a dried cellulose composite film.
[0058] 3) Prepare a real-time state piezoelectric nanogenerator for fruit and vegetable logistics transportation process. A circular film with a radius of 1.5 cm was cut from the dried cellulose acetate / BCZT ceramic composite film. Two copper electrodes with a radius of 1.2 cm were then cut, followed by two 20 cm long wires. The insulating adhesive on the two wires was removed by 5 cm to expose the conductive copper wires inside. These wires were then spirally coiled and attached to the two copper electrodes, and finally, perfectly aligned, attached to both sides of the circular composite film. After attachment, a piezoelectric nanogenerator was obtained.
[0059] Comparative Example 2 A method for fabricating a piezoelectric nanogenerator includes the following steps: 1) Solid-state method for preparing BCZT ceramic T-phase nanoparticle fillers 12.560g BaCO3, 1.124g CaCO3, 0.923g ZrO2, and 5.393g TiO2 in solid form were added to a ball mill jar, along with 30.0g of grinding stones and 40.0ml of alcohol. The mixture was thoroughly combined, and the jar was then placed in a ball mill and milled for 12 hours. After milling, the resulting mixture was dried in an oven to allow the alcohol to evaporate completely. The mixture was then ground in a grinding bowl to pulverize the powder. The powder was then separated from the grinding stones using a sieve. The separated powder was poured into a crucible, covered, and sintered in a muffle furnace at 1450℃ with a heating rate of 5℃ / min and a holding time of 2 hours. The sintered powder was then removed and ground in a grinding bowl to ensure thorough dispersion, yielding pre-sintered BCZT ceramic T-phase nanoparticles. The pre-fired BCZT ceramic particles were added to a ball mill jar with 30.0g of ball stones and 40.0ml of alcohol. The mixture was thoroughly mixed, and then the ball mill jar was placed on a ball mill for a second ball milling for 8 hours. After that, the mixture obtained after ball milling was placed in an oven to dry, allowing the alcohol to evaporate completely. Then, 7.8g of PVA was added for granulation.
[0060] The granulated ceramics were filtered through a 120-mesh sieve, and the filtered ceramic particles had a diameter of approximately 0.125-0.28 mm. Each time, 0.45 g of sample was weighed using an electronic balance and pressed into round green discs by a powder press at a pressure of 20 N. The round green discs were then placed in a muffle furnace for debinding, with the temperature set at 800℃, a heating rate of 5℃ / min, and a holding time of 2 h.
[0061] After debinding, the ceramic sheets were formally sintered in a muffle furnace at a temperature of 1500℃, a heating rate of 5℃ / min, and a holding time of 2h. The sintered ceramic sheets were then removed and ground in a grinding chamber for 40min. After grinding, they were added to a ball mill jar at a mass ratio of ceramic to ball milling stone of 1:1.5, and then alcohol at a volume ratio of 2 was added. After ball milling for 1h, the jar was dried in an oven to obtain BCZT ceramic T-phase nanoparticle filler.
[0062] 2) Preparation of cellulose acetate solution Prepare a solution by mixing 6.66g of DMAc solution with 3.33g of acetone solution at a mass ratio of 3:2, then add 0.24g of PVP, and then place the mixture on a magnetic stirrer and stir at 500r / min for 40min to obtain a clear, transparent solution without particles. Add 0.96 g CA to the obtained mixed solution and stir at 500 r / min for 4 h to obtain a viscous cellulose acetate solution.
[0063] 3) Preparation of cellulose acetate / BCZT electrospinning precursor solution 0.01g of BCZT ceramic T phase was added to a cellulose acetate solution and sonicated for 4h to uniformly disperse the ceramic in the cellulose acetate solution, thus obtaining a cellulose acetate / BCZT electrospinning precursor solution.
[0064] 4) Preparation of cellulose acetate / BCZT ceramic composite films The obtained precursor solution was injected into the needle of a syringe with an inner diameter of 0.41 mm (22G), the injection speed was 0.01 mm / s, the voltage was 18 kV, the roller speed was 700 rpm, and the receiving distance was 21 cm.
[0065] The obtained composite film was dried at room temperature for 12 hours or more to obtain a dried cellulose composite film.
[0066] 5) Fabrication of a piezoelectric nanogenerator A circular film with a radius of 1.5 cm was cut from the dried cellulose acetate / BCZT ceramic composite film. Two copper electrodes with a radius of 1.2 cm were then cut, followed by two 20 cm long wires. The insulating adhesive on the two wires was removed by 5 cm to expose the conductive copper wires inside. These wires were then spirally coiled and attached to the two copper electrodes, and finally, perfectly aligned, attached to both sides of the circular composite film. After attachment, a piezoelectric nanogenerator was obtained.
[0067] Comparative Example 3 A piezoelectric nanogenerator includes the following steps: 1) Solid-state method for preparing BCZT ceramic R-phase nanoparticle fillers First, 13.545g BaCO3, 0.362g CaCO3, 0.89g ZrO2, and 5.204g TiO2 in solid form were added to a ball mill jar, along with 30.0g of grinding stones and 40.0ml of alcohol. The mixture was thoroughly combined, and then the jar was placed in a ball mill and milled for 12 hours. After milling, the resulting mixture was dried in an oven to allow the alcohol to evaporate completely. The mixture was then ground in a grinding bowl to pulverize the powder. The powder was then separated from the grinding stones using a sieve. The separated powder was poured into a crucible, covered, and sintered in a muffle furnace at 1500℃ with a heating rate of 5℃ / min and a holding time of 2 hours. The sintered powder was then removed and ground in a grinding bowl to ensure thorough dispersion, yielding pre-sintered BCZT ceramic R-phase nanoparticles. The pre-fired BCZT ceramic particles were added to a ball mill jar with 30.0g of ball stones and 40.0ml of alcohol. The mixture was thoroughly mixed, and then the ball mill jar was placed on a ball mill for a second ball milling for 8 hours. After that, the mixture obtained after ball milling was placed in an oven to dry, allowing the alcohol to evaporate completely. Then, 7.8g of PVA was added for granulation.
[0068] The granulated ceramics were filtered through a 120-mesh sieve, and the filtered ceramic particles had a diameter of approximately 0.125-0.28 mm. Each time, 0.45 g of sample was weighed using an electronic balance and pressed into round green discs by a powder press at a pressure of 20 N. The round green discs were then placed in a muffle furnace for debinding, with the temperature set at 800℃, a heating rate of 5℃ / min, and a holding time of 2 h.
[0069] After debinding, the ceramic sheets were formally sintered in a muffle furnace at a temperature of 1480℃, a heating rate of 5℃ / min, and a holding time of 2h. The sintered ceramic sheets were then removed and ground in a grinding chamber for 40min. After grinding, the sheets were added to a ball mill jar at a mass ratio of ceramic to ball milling stone of 1:1.5, and then alcohol at a volume ratio of 2 was added. After ball milling for 1h, the sheets were dried in an oven to obtain BCZT ceramic R-phase nanoparticle filler.
[0070] 2) Preparation of cellulose acetate solution Prepare a solution by mixing 6.66g DMAc solution and 3.33g acetone solution at a mass ratio of 3:2, then add 0.24g PVP, and then place the mixture on a magnetic stirrer and stir at 500r / min for 35 min to obtain a clear, transparent, particle-free solution. Add 0.96 g CA to the obtained mixed solution and stir at 500 r / min for 4 h to obtain a viscous cellulose acetate solution.
[0071] 3) Preparation of cellulose acetate / BCZT electrospinning precursor solution 0.01 g of BCZT ceramic R phase was added to a cellulose acetate solution and sonicated for 4 h to uniformly disperse the ceramic in the cellulose acetate solution, thus obtaining a cellulose acetate / BCZT electrospinning precursor solution.
[0072] 4) Preparation of cellulose acetate / BCZT ceramic composite films The obtained precursor solution was injected into the needle of a syringe with an inner diameter of 0.41 mm (22G), the injection speed was 0.01 mm / s, the voltage was 18 kV, the roller speed was 700 rpm, and the receiving distance was 21 cm.
[0073] The obtained composite film was dried at room temperature for 12 hours or more to obtain a dried cellulose composite film.
[0074] 5) Fabrication of a piezoelectric nanogenerator A circular film with a radius of 1.5 cm was cut from the dried cellulose acetate / BCZT ceramic composite film. Two copper electrodes with a radius of 1.2 cm were then cut, followed by two 20 cm long wires. The insulating adhesive on the two wires was removed by 5 cm to expose the conductive copper wires inside. These wires were then spirally coiled and attached to the two copper electrodes, and finally, perfectly aligned, attached to both sides of the circular composite film. After attachment, a piezoelectric nanogenerator was obtained.
[0075] Figure 1 The figures show the composition and morphology of the various materials prepared in Example 1 of this invention. Among them, (a) is the XRD pattern of BCZT ceramic T-phase nanoparticle filler and BCZT ceramic R-phase nanoparticle filler; (b) is the Rietveld refined image of the XRD data of BCZT ceramic T-phase nanoparticle filler and BCZT ceramic R-phase nanoparticle filler, which shows that BCZT ceramic T-phase and BCZT ceramic R-phase have been successfully prepared; (c) is the SEM image of BCZT ceramic nanoparticle filler R-phase; (d) is the SEM image of cellulose acetate / BCZT ceramic composite film. It can be seen from the figures that the prepared fibers are uniform and straight, and the nanofiber network structure formed during the electrospinning process significantly improves the device's real-time sensing ability to external mechanical stimuli.
[0076] Figure 2 The figures show the performance of the piezoelectric nanogenerator prepared in Example 1 of this invention under different frequencies and forces; where (a) is the short-circuit current; (b) is the open-circuit voltage; (c) is the long-term current output diagram; and (d) is the response time. As can be seen from the figures, the prepared piezoelectric nanogenerator can maintain a certain electrical output capability under long-term application conditions, demonstrating the stability of its performance. The short response time of the prepared piezoelectric nanogenerator means that the device has the ability to quickly generate electrical signals in response to rapidly changing mechanical stimuli.
[0077] Figure 3 This diagram illustrates the specific applications of the piezoelectric nanogenerators prepared in Comparative Examples 2 and 3 of this invention. Six prepared PENG sensing units were fixed to the six sides of the inside of a packaging box and connected to a signal acquisition system. The packaging box was then placed on a stool or platform, and the object to be tested was placed inside. Typical conditions during transportation, such as smooth travel, slight vibration, and severe bumps, were simulated by manually applying shaking of different amplitudes and frequencies. During the test, the open-circuit voltage and short-circuit current signals of each PENG unit were recorded in real time. Based on the response amplitude and variation patterns of the sensors in each direction under different conditions, the collision situation between the object inside the packaging and the inner walls of the box, as well as the transportation status, were analyzed, enabling real-time monitoring and identification of vibration and impact during transportation. (a) is a schematic diagram of transportation vibration simulation, which simulates the mechanical vibration experienced during transportation by applying different degrees of artificial shaking to the packaging box; (b) is a schematic diagram of the arrangement of the six-sided sensors, in which CA-R10T0 (representing the ratio of R phase to T phase in the cellulose acetate / BCZT ceramic composite film is 10:0, i.e., the pure R phase of Comparative Example 3) composite film is pasted on the top and bottom to monitor vertical impact and compression; CA-R0T10 (representing the ratio of R phase to T phase in the cellulose acetate / BCZT ceramic composite film is 0:10, i.e., the pure T phase of Comparative Example 2) composite film is pasted on the front, back, left and right sides to monitor lateral vibration, tilt and collision, realizing all-round monitoring of the packaging box in six directions; (c) is a physical picture of the completed intelligent packaging monitoring system, in which each PENG sensor unit is fixed to the inner wall of the packaging box and connected to an external signal acquisition system to realize real-time signal acquisition during transportation. (d1) shows the short-circuit current output of the packaging box under slight shaking conditions, and (d2) shows the open-circuit voltage output of the packaging box under slight shaking conditions. Because the transportation process is relatively stable, the objects inside the packaging only experience slight displacement, mainly making limited contact with the side walls. Therefore, the output signal amplitude is small and the fluctuations are relatively stable. (e1) shows the short-circuit current of the packaging box under severe shaking conditions, and (e2) shows the open-circuit voltage output of the packaging box under severe shaking conditions. At this time, the objects inside the packaging collide frequently with multiple inner walls under inertia, and each sensing unit produces a significant response. The output current and voltage both increase significantly, indicating that the six-sided PENG array can effectively sense mechanical impacts of different directions and intensities during transportation, achieving real-time monitoring of the transportation status.
[0078] Example 2 A method for fabricating a piezoelectric nanogenerator includes the following steps: 1) Solid-state method for preparing BCZT ceramic T-phase nanoparticle fillers First, 12.560g of solid BaCO3, 1.124g of CaCO3, 0.923g of ZrO2, and 5.393g of TiO2 were added to a ball mill jar, along with 30.0g of grinding stones and 40.0ml of alcohol. The mixture was thoroughly combined, and then the jar was placed in a ball mill and milled for 12 hours. After milling, the resulting mixture was dried in an oven to allow the alcohol to evaporate completely. The mixture was then ground in a grinding bowl to pulverize the powder. The powder was then separated from the grinding stones using a sieve. The separated powder was poured into a crucible, covered, and sintered in a muffle furnace at 1450℃ with a heating rate of 5℃ / min and a holding time of 2 hours. The sintered powder was then removed and ground in a grinding bowl to ensure thorough dispersion, yielding pre-sintered BCZT ceramic T-phase nanoparticles. The pre-fired BCZT ceramic particles were added to a ball mill jar with 30.0g of ball stones and 40.0ml of alcohol. The mixture was thoroughly mixed, and then the ball mill jar was placed on a ball mill for a second ball milling for 8 hours. After that, the mixture obtained after ball milling was placed in an oven to dry, allowing the alcohol to evaporate completely. Then, 7.8g of PVA was added for granulation.
[0079] The granulated ceramics were filtered through a 120-mesh sieve, and the filtered ceramic particles had a diameter of approximately 0.125-0.28 mm. Each time, 0.45 g of sample was weighed using an electronic balance and pressed into round green discs by a powder press at a pressure of 20 N. The round green discs were then placed in a muffle furnace for debinding, with the temperature set at 800℃, a heating rate of 5℃ / min, and a holding time of 2 h.
[0080] After debinding, the ceramic sheets were formally sintered in a muffle furnace at a temperature of 1500℃, a heating rate of 5℃ / min, and a holding time of 2h. The sintered ceramic sheets were then removed and ground in a grinding chamber for 40min. After grinding, they were added to a ball mill jar at a mass ratio of ceramic to ball milling stone of 1:1.5, and then alcohol at a volume ratio of 2 was added. After ball milling for 1h, the jar was dried in an oven to obtain BCZT ceramic T-phase nanoparticle filler.
[0081] 2) Solid-state method for preparing BCZT ceramic R-phase nanoparticle fillers First, 13.545g BaCO3, 0.362g CaCO3, 0.89g ZrO2, and 5.204g TiO2 in solid form were added to a ball mill jar, along with 30.0g of grinding stones and 40.0ml of alcohol. The mixture was thoroughly combined, and then the jar was placed in a ball mill and milled for 12 hours. After milling, the resulting mixture was dried in an oven to allow the alcohol to evaporate completely. The mixture was then ground in a grinding bowl to pulverize the powder. The powder was then separated from the grinding stones using a sieve. The separated powder was poured into a crucible, covered, and sintered in a muffle furnace at 1500℃ with a heating rate of 5℃ / min and a holding time of 2 hours. The sintered powder was then removed and ground in a grinding bowl to ensure thorough dispersion, yielding pre-sintered BCZT ceramic R-phase nanoparticles. The pre-fired BCZT ceramic particles were added to a ball mill jar with 30.0g of ball stones and 40.0ml of alcohol. The mixture was thoroughly mixed, and then the ball mill jar was placed on a ball mill for a second ball milling for 8 hours. After that, the mixture obtained after ball milling was placed in an oven to dry, allowing the alcohol to evaporate completely. Then, 7.8g of PVA was added for granulation.
[0082] The granulated ceramics were filtered through a 120-mesh sieve, and the filtered ceramic particles had a diameter of approximately 0.125-0.28 mm. Each time, 0.45 g of sample was weighed using an electronic balance and pressed into round green discs by a powder press at a pressure of 20 N. The round green discs were then placed in a muffle furnace for debinding, with the temperature set at 800℃, a heating rate of 5℃ / min, and a holding time of 2 h.
[0083] After debinding, the ceramic sheets were formally sintered in a muffle furnace at a temperature of 1480℃, a heating rate of 5℃ / min, and a holding time of 2h. The sintered ceramic sheets were then removed and ground in a grinding chamber for 40min. After grinding, the sheets were added to a ball mill jar at a mass ratio of ceramic to ball milling stone of 1:1.5, and then alcohol at a volume ratio of 2 was added. After ball milling for 1h, the sheets were dried in an oven to obtain BCZT ceramic R-phase nanoparticle filler.
[0084] 3) Preparation of cellulose acetate solution Prepare a solution by mixing 6.66g of DMAc solution with 3.33g of acetone solution at a mass ratio of 3:2, then add 0.24g of PVP, and then place the mixture on a magnetic stirrer and stir at 500r / min for 40min to obtain a clear, transparent, particle-free solution. Add 0.96 g CA to the obtained mixed solution and stir at 500 r / min for 4.5 h to obtain a viscous cellulose acetate solution.
[0085] 4) Preparation of cellulose acetate / BCZT electrospinning precursor solution 0.007 g of BCZT ceramic T phase and 0.003 g of BCZT ceramic R phase were added to a cellulose acetate solution and sonicated for 4.5 h to uniformly disperse the ceramics in the cellulose acetate solution, thus obtaining a cellulose acetate / BCZT electrospinning precursor solution.
[0086] 5) Preparation of cellulose acetate / BCZT ceramic composite films The obtained precursor solution was injected into the needle of a syringe with an inner diameter of 0.41 mm (22G), the injection speed was 0.01 mm / s, the voltage was 17 kV, the roller speed was 700 rpm, and the receiving distance was 22 cm.
[0087] The obtained composite film was dried at room temperature for 12 hours or more to obtain a dried cellulose composite film.
[0088] 6) Fabrication of a piezoelectric nanogenerator A circular film with a radius of 1.5 cm was cut from the dried cellulose acetate / BCZT ceramic composite film. Two copper electrodes with a radius of 1.2 cm were then cut, followed by two 20 cm long wires. The insulating adhesive on the two wires was removed by 5 cm to expose the conductive copper wires inside. These wires were then spirally coiled and attached to the two copper electrodes, and finally, perfectly aligned, attached to both sides of the circular composite film. After attachment, a piezoelectric nanogenerator was obtained.
[0089] Example 3 A method for fabricating a piezoelectric nanogenerator includes the following steps: 1) Solid-state method for preparing BCZT ceramic T-phase nanoparticle fillers First, 12.560g of solid BaCO3, 1.124g of CaCO3, 0.923g of ZrO2, and 5.393g of TiO2 were added to a ball mill jar, along with 30.0g of grinding stones and 40.0ml of alcohol. The mixture was thoroughly combined, and then the jar was placed in a ball mill and milled for 12 hours. After milling, the resulting mixture was dried in an oven to allow the alcohol to evaporate completely. The mixture was then ground in a grinding bowl to pulverize the powder. The powder was then separated from the grinding stones using a sieve. The separated powder was poured into a crucible, covered, and sintered in a muffle furnace at 1450℃ with a heating rate of 5℃ / min and a holding time of 2 hours. The sintered powder was then removed and ground in a grinding bowl to ensure thorough dispersion, yielding pre-sintered BCZT ceramic T-phase nanoparticles. The pre-fired BCZT ceramic particles were added to a ball mill jar with 30.0g of ball stones and 40.0ml of alcohol. The mixture was thoroughly mixed, and then the ball mill jar was placed on a ball mill for a second ball milling for 8 hours. After that, the mixture obtained after ball milling was placed in an oven to dry, allowing the alcohol to evaporate completely. Then, 7.8g of PVA was added for granulation.
[0090] The granulated ceramics were filtered through a 120-mesh sieve, and the filtered ceramic particles had a diameter of approximately 0.125-0.28 mm. Each time, 0.45 g of sample was weighed using an electronic balance and pressed into round green discs by a powder press at a pressure of 20 N. The round green discs were then placed in a muffle furnace for debinding, with the temperature set at 800℃, a heating rate of 5℃ / min, and a holding time of 2 h.
[0091] After debinding, the ceramic sheets were formally sintered in a muffle furnace at a temperature of 1500℃, a heating rate of 5℃ / min, and a holding time of 2h. The sintered ceramic sheets were then removed and ground in a grinding chamber for 40min. After grinding, they were added to a ball mill jar at a mass ratio of ceramic to ball milling stone of 1:1.5, and then alcohol at a volume ratio of 2 was added. After ball milling for 1h, the jar was dried in an oven to obtain BCZT ceramic T-phase nanoparticle filler.
[0092] 2) Solid-state method for preparing BCZT ceramic R-phase nanoparticle fillers First, 13.545g BaCO3, 0.362g CaCO3, 0.89g ZrO2, and 5.204g TiO2 in solid form were added to a ball mill jar, along with 30.0g of grinding stones and 40.0ml of alcohol. The mixture was thoroughly combined, and then the jar was placed in a ball mill and milled for 12 hours. After milling, the resulting mixture was dried in an oven to allow the alcohol to evaporate completely. The mixture was then ground in a grinding bowl to pulverize the powder. The powder was then separated from the grinding stones using a sieve. The separated powder was poured into a crucible, covered, and sintered in a muffle furnace at 1500℃ with a heating rate of 5℃ / min and a holding time of 2 hours. The sintered powder was then removed and ground in a grinding bowl to ensure thorough dispersion, yielding pre-sintered BCZT ceramic R-phase nanoparticles. The pre-fired BCZT ceramic particles were added to a ball mill jar with 30.0g of ball stones and 40.0ml of alcohol. The mixture was thoroughly mixed, and then the ball mill jar was placed on a ball mill for a second ball milling for 8 hours. After that, the mixture obtained after ball milling was placed in an oven to dry, allowing the alcohol to evaporate completely. Then, 7.8g of PVA was added for granulation.
[0093] The granulated ceramics were filtered through a 120-mesh sieve, and the filtered ceramic particles had a diameter of approximately 0.125-0.28 mm. Each time, 0.45 g of sample was weighed using an electronic balance and pressed into round green discs by a powder press at a pressure of 20 N. The round green discs were then placed in a muffle furnace for debinding, with the temperature set at 800℃, a heating rate of 5℃ / min, and a holding time of 2 h.
[0094] After debinding, the ceramic sheets were formally sintered in a muffle furnace at a temperature of 1480℃, a heating rate of 5℃ / min, and a holding time of 2h. The sintered ceramic sheets were then removed and ground in a grinding chamber for 40min. After grinding, the sheets were added to a ball mill jar at a mass ratio of ceramic to ball milling stone of 1:1.5, and then alcohol at a volume ratio of 2 was added. After ball milling for 1h, the sheets were dried in an oven to obtain BCZT ceramic R-phase nanoparticle filler.
[0095] 3) Preparation of cellulose acetate solution Prepare a solution by mixing 6.66 g of DMAc solution with 3.33 g of acetone solution at a mass ratio of 3:2, then add 0.24 g of PVP, and then place the mixture on a magnetic stirrer and stir at 500 r / min for 40 min to obtain a clear, transparent, particle-free solution. Add 0.96 g CA to the obtained mixed solution and stir at 500 r / min for 4.5 h to obtain a viscous cellulose acetate solution.
[0096] 4) Preparation of cellulose acetate / BCZT electrospinning precursor solution 0.003 g of BCZT ceramic T phase and 0.007 g of BCZT ceramic R phase were added to a cellulose acetate solution and sonicated for 4 h to uniformly disperse the ceramics in the cellulose acetate solution, thus obtaining a cellulose acetate / BCZT electrospinning precursor solution.
[0097] 5) Preparation of cellulose acetate / BCZT ceramic composite films The obtained precursor solution was injected into the needle of a syringe with an inner diameter of 0.41 mm (22G), the injection speed was 0.01 mm / s, the voltage was 17 kV, the roller speed was 700 rpm, and the receiving distance was 22 cm.
[0098] The obtained composite film was dried at room temperature for 12 hours or more to obtain a dried cellulose composite film.
[0099] 6) Fabrication of a piezoelectric nanogenerator A circular film with a radius of 1.5 cm was cut from the dried cellulose acetate / BCZT ceramic composite film. Two copper electrodes with a radius of 1.2 cm were then cut, followed by two 20 cm long wires. The insulating adhesive on the two wires was removed by 5 cm to expose the conductive copper wires inside. These wires were then spirally coiled and attached to the two copper electrodes, and finally, perfectly aligned, attached to both sides of the circular composite film. After attachment, a piezoelectric nanogenerator was obtained.
[0100] Example 4 A method for fabricating a piezoelectric nanogenerator includes the following steps: 1) Solid-state method for preparing BCZT ceramic T-phase nanoparticle fillers First, 11.968g of solid BaCO3, 1.374g of CaCO3, 0.836g of ZrO2, and 5.847g of TiO2 were added to a ball mill jar (BaCO3:CaCO3:TiO2:ZrO2 molar ratio = 16:3:18:1). At the same time, 30.0g of ball stones and 40.0ml of alcohol were added to the ball mill jar, and the mixture was thoroughly mixed. Then, the ball mill jar was placed on a ball mill and milled for 8 hours. After that, the mixture obtained after milling was placed in an oven to dry, allowing the alcohol to evaporate completely. The resulting mixture was then ground in a grinding mortar to crush the powder. The powder was then separated from the grinding stones using a sieve. The separated powder was poured into a crucible, covered, and placed in a muffle furnace for pre-firing. The muffle furnace temperature was set to 1445℃, the heating rate was 4℃ / min, and the holding time was 2 hours. The pre-firing powder was then removed and ground in a grinding mill to ensure complete dispersion, yielding pre-fired BCZT ceramic T-phase nanoparticles. The pre-fired BCZT ceramic particles were added to a ball mill jar, along with 30.0g of grinding stones and 40.0ml of alcohol. The mixture was thoroughly mixed, and then the jar was ball-milled a second time for 6 hours. The resulting mixture was then dried in an oven to allow the alcohol to evaporate completely. Finally, 7g of PVA was added for granulation.
[0101] The granulated ceramics were filtered through a 120-mesh sieve to obtain ceramic particles with a diameter of approximately 0.125~0.28mm. Each time, 0.45g of sample was weighed using an electronic balance and pressed into round green discs by a powder press at a pressure of 20N. The round green discs were then placed in a muffle furnace for debinding. The temperature was set to 790℃, the heating rate was 4℃ / min, and the holding time was 2h.
[0102] After debinding, the ceramic sheets were formally sintered in a muffle furnace at a temperature of 1470℃, a heating rate of 4℃ / min, and a holding time of 2h. The sintered ceramic sheets were then removed and ground in a grinding chamber for 30min. After grinding, they were added to a ball mill jar at a mass ratio of ceramic to ball milling stone of 1:1.5, and then alcohol at a volume ratio of 2 was added. After ball milling for 2h, the jar was dried in an oven to obtain BCZT ceramic T-phase nanoparticle filler.
[0103] 2) Solid-state method for preparing BCZT ceramic R-phase nanoparticle fillers Using the same conditions and parameters as in step 2) of Example 1, BCZT ceramic R-phase nanoparticle filler was obtained.
[0104] 3) Preparation of cellulose acetate solution Prepare a mixed solvent by mixing 8.00g of DMAc solution and 2.00g of acetone solution at a mass ratio of 4:1, then add 0.24g of PVP. Place the mixed solution on a magnetic stirrer and stir at 500r / min for 40min to obtain a clear, transparent, particle-free solution. Add 0.96g of CA to the above mixed solution and stir at 500r / min for 4.5h to obtain a viscous cellulose acetate solution.
[0105] 4) Preparation of cellulose acetate / BCZT electrospinning precursor solution 0.005 g of BCZT ceramic T phase and 0.005 g of BCZT ceramic R phase were added to a cellulose acetate solution and sonicated for 5 h to uniformly disperse the ceramics in the cellulose acetate solution, thus obtaining a cellulose acetate / BCZT electrospinning precursor solution.
[0106] 5) Preparation of cellulose acetate / BCZT ceramic composite films The obtained precursor solution was injected into a syringe needle with an inner diameter of 0.41 mm (22G) at an injection speed of 0.01 mm / s, a voltage of 16 kV, a roller speed of 700 rpm, and a receiving distance of 23 cm. The resulting composite film was dried at room temperature for 12 hours or more to obtain a dried cellulose acetate / BCZT ceramic composite film.
[0107] 6) Fabrication of piezoelectric nanogenerators The piezoelectric nanogenerator was assembled according to the method in step 6 of Example 1.
[0108] Example 5 A method for fabricating a piezoelectric nanogenerator includes the following steps: 1) Solid-state method for preparing BCZT ceramic T-phase nanoparticle fillers First, 12.710g of solid BaCO3, 0.890g of CaCO3, 1.110g of ZrO2, and 5.372g of TiO2 were added to a ball mill jar (BaCO3:CaCO3:TiO2:ZrO2 molar ratio = 17:2:17.5:2). At the same time, 30.0g of ball stones and 40.0ml of alcohol were added to the ball mill jar and mixed thoroughly. Then, the ball mill jar was placed on a ball mill and milled for 16 hours. After that, the mixture obtained after milling was placed in an oven to dry, allowing the alcohol to evaporate completely. The resulting mixture was then ground in a grinding mortar to crush the powder. The powder was then separated from the grinding stones using a sieve. The separated powder was poured into a crucible, covered, and placed in a muffle furnace for pre-firing. The muffle furnace temperature was set to 1455℃, the heating rate was 5℃ / min, and the holding time was 2 hours. The pre-firing powder was then removed and ground in a grinding mortar to ensure complete dispersion, yielding pre-fired BCZT ceramic T-phase nanoparticles. The pre-fired BCZT ceramic particles were then added to a ball mill jar, along with 30.0g of grinding stones and 40.0ml of alcohol. The mixture was thoroughly mixed, and then the jar was placed in a ball mill for a second ball milling process for 10 hours. The resulting mixture was then dried in an oven to allow the alcohol to evaporate completely. Finally, 9g of PVA was added for granulation.
[0109] The granulated ceramics were filtered through a 120-mesh sieve to obtain ceramic particles with a diameter of approximately 0.125~0.28mm. Each time, 0.45g of sample was weighed using an electronic balance and pressed into round green discs by a powder press at a pressure of 20N. The round green discs were then placed in a muffle furnace for debinding. The temperature was set to 810℃, the heating rate was 5℃ / min, and the holding time was 2h.
[0110] After debinding, the ceramic sheets were formally sintered in a muffle furnace at a temperature of 1530℃, a heating rate of 5℃ / min, and a holding time of 2h. The sintered ceramic sheets were then removed and ground in a grinding chamber for 60min. After grinding, they were added to a ball mill jar at a mass ratio of ceramic to ball milling stone of 1:1.5, and then alcohol at a volume ratio of 2 was added. After ball milling for 1h, the jar was dried in an oven to obtain BCZT ceramic T-phase nanoparticle filler.
[0111] 2) Solid-state method for preparing BCZT ceramic R-phase nanoparticle fillers Using the same conditions and parameters as in step 2) of Example 1, BCZT ceramic R-phase nanoparticle filler was obtained.
[0112] 3) Preparation of cellulose acetate solution Prepare a mixed solvent by mixing 6.00g of DMAc solution and 2.00g of acetone solution at a mass ratio of 3:1, then add 0.24g of PVP. Place the mixed solution on a magnetic stirrer and stir at 600r / min for 30min to obtain a clear, transparent, particle-free solution. Add 0.96g of CA to the above mixed solution and stir at 600r / min for 4h to obtain a viscous cellulose acetate solution.
[0113] 4) Preparation of cellulose acetate / BCZT electrospinning precursor solution 0.005 g of BCZT ceramic T phase and 0.005 g of BCZT ceramic R phase were added to a cellulose acetate solution and sonicated for 4 h to uniformly disperse the ceramics in the cellulose acetate solution, thus obtaining a cellulose acetate / BCZT electrospinning precursor solution.
[0114] 5) Preparation of cellulose acetate / BCZT ceramic composite films The obtained precursor solution was injected into a syringe needle with an inner diameter of 0.41 mm (22G) at an injection speed of 0.01 mm / s, a voltage of 16 kV, a roller speed of 700 rpm, and a receiving distance of 20 cm. The resulting composite film was dried at room temperature for 12 hours or more to obtain a dried cellulose acetate / BCZT ceramic composite film.
[0115] 6) Fabrication of piezoelectric nanogenerators The piezoelectric nanogenerator was assembled according to the method in step 6 of Example 1.
[0116] Example 6 A method for fabricating a piezoelectric nanogenerator includes the following steps: 1) Solid-state method for preparing BCZT ceramic T-phase nanoparticle fillers Using the same conditions and parameters as in step 1) of Example 1, BCZT ceramic T-phase nanoparticle fillers were obtained.
[0117] 2) Solid-state method for preparing BCZT ceramic R-phase nanoparticle fillers First, 14.070g of solid BaCO3, 0.362g of CaCO3, 0.863g of ZrO2, and 5.469g of TiO2 were added to a ball mill jar (BaCO3:CaCO3:TiO2:ZrO2 molar ratio = 20:1:18.5:2.5). At the same time, 30.0g of ball stones and 40.0ml of alcohol were added to the ball mill jar, and the mixture was thoroughly mixed. Then, the ball mill jar was placed on a ball mill and milled for 8 hours. After that, the mixture obtained after milling was placed in an oven to dry, allowing the alcohol to evaporate completely. The resulting mixture was then ground in a grinding mortar to crush the powder. The powder was then separated from the grinding stones using a sieve. The separated powder was poured into a crucible, covered, and placed in a muffle furnace for pre-firing. The muffle furnace temperature was set to 1520℃, the heating rate was 5℃ / min, and the holding time was 2 hours. The pre-firing powder was then removed and ground in a grinding mortar to ensure complete dispersion, yielding pre-fired BCZT ceramic R-phase nanoparticles. The pre-fired BCZT ceramic particles were added to a ball mill jar, along with 30.0g of grinding stones and 40.0ml of alcohol. The mixture was thoroughly mixed, and then the jar was placed in a ball mill for a second ball milling process for 10 hours. The resulting mixture was then dried in an oven to allow the alcohol to evaporate completely. Finally, 8g of PVA was added for granulation.
[0118] The granulated ceramics were filtered through a 120-mesh sieve to obtain ceramic particles with a diameter of approximately 0.125~0.28mm. Each time, 0.45g of sample was weighed using an electronic balance and pressed into round green discs by a powder press at a pressure of 20N. The round green discs were then placed in a muffle furnace for debinding. The temperature was set to 800℃, the heating rate was 5℃ / min, and the holding time was 2h.
[0119] After debinding, the ceramic sheets were formally sintered in a muffle furnace at a temperature of 1510℃, a heating rate of 5℃ / min, and a holding time of 2h. The sintered ceramic sheets were then removed and ground in a grinding chamber for 40min. After grinding, they were added to a ball mill jar at a mass ratio of ceramic to ball milling stone of 1:1.5, and then alcohol at a volume ratio of 2 was added. After ball milling for 1h, the jar was dried in an oven to obtain BCZT ceramic R-phase nanoparticle filler.
[0120] 3) Preparation of cellulose acetate solution A cellulose acetate solution was obtained using the same conditions and parameters as in step 3) of Example 1.
[0121] 4) Preparation of cellulose acetate / BCZT electrospinning precursor solution 0.003 g of BCZT ceramic T phase and 0.003 g of BCZT ceramic R phase were added to a cellulose acetate solution and sonicated for 4.5 h to uniformly disperse the ceramics in the cellulose acetate solution, thus obtaining a cellulose acetate / BCZT electrospinning precursor solution.
[0122] 5) Preparation of cellulose acetate / BCZT ceramic composite films The obtained precursor solution was injected into a syringe needle with an inner diameter of 0.41 mm (22G) at an injection speed of 0.01 mm / s, a voltage of 16 kV, a roller speed of 700 rpm, and a receiving distance of 22 cm. The resulting composite film was dried at room temperature for 12 hours or more to obtain a dried cellulose acetate / BCZT ceramic composite film.
[0123] 6) Fabrication of piezoelectric nanogenerators The piezoelectric nanogenerator was assembled according to the method in step 6 of Example 1.
[0124] Example 7 A method for fabricating a piezoelectric nanogenerator includes the following steps: 1) Solid-state method for preparing BCZT ceramic T-phase nanoparticle fillers Using the same conditions and parameters as in step 1) of Example 1, BCZT ceramic T-phase nanoparticle fillers were obtained.
[0125] 2) Solid-state method for preparing BCZT ceramic R-phase nanoparticle fillers First, 14.070g of solid BaCO3, 0.433g of CaCO3, 0.756g of ZrO2, and 5.704g of TiO2 were added to a ball mill jar (BaCO3:CaCO3:TiO2:ZrO2 molar ratio = 19:1.5:19:2). At the same time, 30.0g of ball stones and 40.0ml of alcohol were added to the ball mill jar and mixed thoroughly. Then, the ball mill jar was placed on a ball mill and milled for 8 hours. After that, the mixture obtained after milling was placed in an oven to dry, allowing the alcohol to evaporate completely. The resulting mixture was then ground in a grinding mortar to crush the powder. The powder was then separated from the grinding stones using a sieve. The separated powder was poured into a crucible, covered, and placed in a muffle furnace for pre-firing. The muffle furnace temperature was set to 1450℃, the heating rate was 4℃ / min, and the holding time was 2 hours. The pre-firing powder was then removed and ground in a grinding mortar to ensure complete dispersion, yielding pre-fired BCZT ceramic R-phase nanoparticles. The pre-fired BCZT ceramic particles were added to a ball mill jar, along with 30.0g of grinding stones and 40.0ml of alcohol. The mixture was thoroughly mixed, and then the jar was ball-milled a second time for 8 hours. The resulting mixture was then dried in an oven to allow the alcohol to evaporate completely. Finally, 7g of PVA was added for granulation.
[0126] The granulated ceramics were filtered through a 120-mesh sieve to obtain ceramic particles with a diameter of approximately 0.125~0.28mm. Each time, 0.45g of sample was weighed using an electronic balance and pressed into round green discs by a powder press at a pressure of 20N. The round green discs were then placed in a muffle furnace for debinding. The temperature was set to 790℃, the heating rate was 4℃ / min, and the holding time was 2h.
[0127] After debinding, the ceramic sheets were formally sintered in a muffle furnace at a temperature of 1450℃, a heating rate of 4℃ / min, and a holding time of 2h. The sintered ceramic sheets were then removed and ground in a grinding chamber for 30min. After grinding, they were added to a ball mill jar at a mass ratio of ceramic to ball milling stone of 1:1.5, and then alcohol at a volume ratio of 2 was added. After ball milling for 1h, the jar was dried in an oven to obtain BCZT ceramic R-phase nanoparticle filler.
[0128] 3) Preparation of cellulose acetate solution A cellulose acetate solution was obtained using the same conditions and parameters as in step 3) of Example 1.
[0129] 4) Preparation of cellulose acetate / BCZT electrospinning precursor solution 0.01g of BCZT ceramic T phase and 0.01g of BCZT ceramic R phase were added to a cellulose acetate solution and sonicated for 4.5h to uniformly disperse the ceramics in the cellulose acetate solution, thus obtaining a cellulose acetate / BCZT electrospinning precursor solution.
[0130] 5) Preparation of cellulose acetate / BCZT ceramic composite films The obtained precursor solution was injected into a syringe needle with an inner diameter of 0.41 mm (22G) at an injection speed of 0.01 mm / s, a voltage of 14 kV, a roller rotation speed of 500 rpm (or 600 rpm, for preparing two samples respectively), and a receiving distance of 22 cm. The resulting composite film was dried at room temperature for 12 hours or more to obtain a dried cellulose acetate / BCZT ceramic composite film.
[0131] 6) Fabrication of piezoelectric nanogenerators The piezoelectric nanogenerator was assembled according to the method in step 6 of Example 1.
[0132] Table 1. Comparison of short-circuit currents of piezoelectric nanogenerators prepared in Examples 1-3 and Comparative Examples 1-3.
[0133] Table 1 compares the short-circuit currents of the piezoelectric nanogenerators prepared in Examples 1-3 and Comparative Examples 1-3. By controlling the excitation frequency and the applied force of the exciter, the short-circuit currents of the piezoelectric nanogenerators prepared in Examples 1-3 and Comparative Examples 1-3 were tested under a fixed force of 2N and an excitation frequency of 5Hz. It can be seen that the short-circuit current of Example 1 is the largest, and the electrical output performance is the best.
[0134] In summary, this invention provides a piezoelectric nanogenerator, its preparation method, and its application in real-time monitoring of fruit and vegetable transportation. Using cellulose acetate as a flexible biomass matrix and BCZT ceramic T-phase nanoparticles and BCZT ceramic R-phase nanoparticles as functional fillers, a nanofiber network structure is constructed through electrospinning. The resulting piezoelectric nanogenerator possesses flexibility, biomass environmental friendliness, and excellent electrical output performance (open-circuit voltage approximately 46V, short-circuit current approximately 3.4μA). It can generate a rapid and stable electrical signal response to weak mechanical stimuli, making it suitable for real-time monitoring of mechanical conditions such as vibration and impact during fruit and vegetable transportation.
[0135] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a piezoelectric nanogenerator, characterized in that, include: BCZT ceramic T-phase nanoparticle filler and BCZT ceramic R-phase nanoparticle filler were respectively added to cellulose acetate solution and dispersed by ultrasonication to obtain cellulose acetate / BCZT electrospinning precursor solution. Electrospinning was performed on the cellulose acetate / BCZT electrospinning precursor solution, and after drying, cellulose acetate / BCZT ceramic composite film was obtained. After cutting the cellulose acetate / BCZT ceramic composite film, it is attached between two copper electrodes, and a conductive copper wire is spirally coiled and attached to the two copper electrodes to obtain a piezoelectric nanogenerator.
2. The method for preparing a piezoelectric nanogenerator according to claim 1, characterized in that, BCZT ceramic T-phase nanoparticle filler was prepared by a solid-state method. The preparation method included: mixing BaCO3, CaCO3, ZrO2 and TiO2, and then sequentially subjecting the mixture to ball milling, drying, grinding, sieving, pre-calcination, secondary ball milling, granulation, filtration, pressing, debinding, sintering, secondary grinding, tertiary ball milling and drying to obtain BCZT ceramic T-phase nanoparticle filler; the molar ratio of BaCO3, CaCO3, TiO2 and ZrO2 was (16~17):(2~3):(17~18):(1~2). BCZT ceramic R-phase nanoparticle filler was prepared by a solid-state method. The preparation method included: mixing BaCO3, CaCO3, ZrO2 and TiO2, and then sequentially subjecting the mixture to ball milling, drying, grinding, sieving, pre-calcination, secondary ball milling, granulation, filtration, pressing, debinding, sintering, secondary grinding, tertiary ball milling and drying to obtain BCZT ceramic R-phase nanoparticle filler; the molar ratio of BaCO3, CaCO3, TiO2 and ZrO2 was (19~20):(1~1.5):(18~19):(2~3); The ball milling time is 8-16 hours; the secondary ball milling time is 6-10 hours; the granulation is carried out by adding polyvinyl alcohol; the granulated ceramics are filtered through a 120-mesh sieve to obtain ceramic particles with a diameter of 0.125-0.28 mm; the glue removal temperature is 790-810℃, the heating rate is 4-5℃ / min, and the holding time is 2 hours; the secondary grinding time is 30-60 minutes, and the tertiary ball milling time is 1-2 hours.
3. The method for preparing a piezoelectric nanogenerator according to claim 2, characterized in that, In the preparation of BCZT ceramic T-phase nanoparticle filler, the pre-calcination temperature is 1445~1455℃; the sintering temperature is 1470~1530℃, the heating rate is 4~5℃ / min, and the holding time is 2h.
4. The method for preparing a piezoelectric nanogenerator according to claim 2, characterized in that, In the preparation of BCZT ceramic R-phase nanoparticle filler, the pre-calcination temperature is 1450~1520℃; the sintering temperature is 1450~1510℃, the heating rate is 4~5℃ / min, and the holding time is 2h.
5. The method for preparing a piezoelectric nanogenerator according to claim 1, characterized in that, A method for preparing cellulose acetate solution includes: mixing N,N-dimethylacetamide solution and acetone solution to prepare a mixed solvent, adding polyvinylpyrrolidone and stirring, then adding cellulose acetate and continuing to stir to obtain cellulose acetate solution.
6. The method for preparing a piezoelectric nanogenerator according to claim 5, characterized in that, The mass ratio of the N,N-dimethylacetamide solution to the acetone solution is (3~4):(1~2); the mass ratio of the polyvinylpyrrolidone to cellulose acetate is 0.24:0.96; the stirring speed before adding cellulose acetate is 500~600 r / min for 30~40 min; the stirring speed after adding cellulose acetate is 500~600 r / min for 4~4.5 h.
7. The method for preparing a piezoelectric nanogenerator according to claim 1, characterized in that, In the cellulose acetate solution, the mass ratio of BCZT ceramic T-phase nanoparticle filler to BCZT ceramic R-phase nanoparticle filler is (0.003~0.01):(0.003~0.01); the ultrasonic dispersion time is 4~5h.
8. The method for preparing a piezoelectric nanogenerator according to claim 1, characterized in that, The electrospinning conditions include: syringe inner diameter of 0.41 mm, injection speed of 0.01 mm / s, voltage of 14~18 kV, roller speed of 500~700 rpm, and receiving distance of 20~23 cm; the drying conditions are to place at room temperature for 12 hours or more.
9. A piezoelectric nanogenerator, characterized in that, It was prepared by the method described in any one of claims 1-8.
10. The application of the piezoelectric nanogenerator according to claim 9 in real-time monitoring of fruit and vegetable transportation.
Citation Information
Patent Citations
A branch-stem heterogeneous structure piezoelectric fiber, piezoelectric nanogenerator, and preparation method and application thereof
CN119287558B
A coupled biomass-based nanogenerator with both PENG and TENG and preparation method thereof
CN119401850B
